Hubungan antara personaliti warna dengan personaliti minat kerjaya - Debra, Adrian. (Universiti Malaysia Sarawak, UNIMAS, 2007)
The purpose of this research is to determine the relationship between color personality and career interest personality. 127 first year UNIMAS students have been chosen using Stratified Random Sampling Technique participated in this research. A questionnaire form with three main section which included demographic factors, Color Personality Inventory (IPW) and Self-Directed Search Inventory (SDS) had been distributed to collect data for this research. The findings were analyzed using SPSS version 11.5 and descriptive statistic was used to measure the frequencies of demographic factors. Apart from it, inferential statistic which included Pearson Correlations, ANOVA, and t-Test were used to test null hypothesis of this study. The result shown that only Orange color personality and Enterprising career interest personality shown no significant relationship while other color personality and career interest personality that being tested shown significant positive correlations relationship. For demographic factors, programmed factor have significant relationship with the career interest personality but gender factor only shown significant relationship with Realistic career interest personality. Finally for the race factor,it shown that there were no significant relationship with the entire career interest personality.